Blockchain and artificial intelligence : the world rewired - James, Tom; James, Tom (De Gruyter, 2021)
Blockchain and artificial intelligence are perhaps the two most significant disruptive technologies this century and both will significantly rewire the world of global financial markets and the world in which we live. While blockchain offers a number of significant advantages over traditional forms of finance including lower cost and massive increases in operational efficiencies of traded markets, property records and a whole host of transaction processes, artificial intelligence is moving fast from basic structured machine learning doing menial yet important big data tasks like credit card fraud detection to predictive analysis and real-time real-world risk management and investment decision making. There is still a lot of confusion in the market about cryptocurrencies, bitcoin and the underlying blockchain technology. Blockchain and Artificial Intelligence highlights the underlying technologies of blockchain and the differences between cryptocurrencies and blockchain financial applications. It explores the current AI offerings and gives a vision of the fast-moving developments in this area including the many solutions that are expected to revolutionize the way financial and commodity markets will operate in the future.